Aarhus Regenerative Orthopaedics Symposium (AROS): Regeneration in the ageing population. (16th December 2016) - Foldager, Casper B; Bendtsen, Michael; Berg, Lise C; Brinchmann, Jan E; Brittberg, Mats; Bunger, Cody; Canseco, Jose; Chen, Li; Christensen, Bjørn B; Colombier, Pauline; Deleuran, Bent W; Edwards, James; et al.
Abstract: The combination of modern interventional and preventive medicine has led to an epidemic of ageing. While this phenomenon is a positive consequence of an improved lifestyle and achievements in a society, the longer life expectancy is often accompanied by decline in quality of life due to musculoskeletal pain and disability. The Aarhus Regenerative Orthopaedics Symposium (AROS) 2015 was motivated by the need to address regenerative challenges in an ageing population by engaging clinicians, basic scientists, and engineers. In this position paper, we review our contemporary understanding of societal, patient-related, and basic science-related challenges in order to provide a reasoned roadmap for the future to deal with this compelling and urgent healthcare problem.